Anti-staphylococcal activity, antibiotic-resistance modulation effects and action of Harungana madagascariensis (Hypericaceae) fruit extracts on the antioxidant system of multidrug-resistant Staphylococcus aureus. - Brenda Ngueffo Tiwa; Aimé Gabriel Fankam; Céline Brinda Sonfack; Richard Mouozong; Michael Francis Kengne; Armelle Tsafack Mbaveng; Victor Kuete (PLoS ONE)
Global public health is facing a real challenge due to infections caused by multidrug-resistant bacteria. Among these bacteria, Staphylococcus aureus is known to rapidly develops antibiotic resistance. This study aimed to evaluate the antibacterial potential of Harungana madagascariensis fruit extracts and their effects on the antioxidant system of multidrug-resistant Staphylococcus aureus. Moreover, the extracts were evaluated for their antibiotic-resistance modulation effects against some multidrug-resistant Staphylococcus aureus. The antibacterial activity of the extracts and their effect in combination with antibiotics were assessed using the micro-dilution method. The catalase activity was assessed by measuring the height of foam, whereas the lipid peroxidation was carried out through spectrophotometric quantification of malondialdehyde. The phytochemical analysis of extracts was carried out using qualitative and quantitative standard assays. The tested extracts showed antibacterial activities, with minimum inhibitory concentrations ranging from 32 to 2048 μg/mL. The most active extract (hexane extract) has inhibited the catalase activity and induced the lipid peroxidation in S. aureus DO18SA, indicating its ability to interact with the antioxidant system of the bacteria. Moreover, the dichloromethane/methanol extract increased by 2-128-fold the activity of levofloxacin, ampicillin, and cefotaxime against selected multidrug-resistant S. aureus. It also showed synergistic effect with cefotaxime against D051SA. Alkaloids, triterpenes, and phenols were detected in all the extracts, whereas the other phytochemical classes were selectively distributed. The methanol extract had the highest phenolic content (142.20 ± 16.75 mg GAE/g of extract). Overall, the findings of this study suggest that extracts of Harungana madagascariensis fruits could be valuable sources of new agents for treating multidrug-resistant Staphylococcus aureus infections.